Inflection Point: The Role of Testing in Admissions Decisions in a Postpandemic Environment. Issue 1 (31st January 2022) - Camara, Wayne J.; Mattern, Krista
Abstract: In 2020, the onset of COVID‐19 greatly restricted access to admissions testing in higher education and required innovative solutions and flexibility such as at home testing with remote proctoring, reducing testing time, pop‐up locations, and additional testing dates. Increased focus on social justice, diversity, and fairness continued to concern admissions professionals during this time. This article is intended to provide an update (Camara) on admissions testing as we enter 2022, documenting enhancements and changes across testing programs. In addition, we report recent data and findings on applications, enrollment, and test taking, as well as the prevalence of test optional and test blind policies and its impact on score sending in undergraduate, graduate, business, law, and medical schools. It is important to note that many questions remain unanswered. Our original intent was to include more information on the impact of test‐optional polices on diversity as we thought the pandemic would be in the rear‐view mirror by now. Given the lingering effects of the pandemic, it will be critical to evaluate the impact of these policies changes on the entering class of 2021 and beyond as those data become available.